Regulation of the Drosophila epidermal growth factor-ligand vein is mediated by multiple domains. - Donaldson, T.; Wang, S.H.; Jacobsen, T.L.; Schnepp, B.; Price, J.; Simcox, A. (Genetics, 2004)
Vein (Vn), a ligand for the Drosophila epidermal growth factor receptor (Egfr), has a complex structure including a PEST, Ig, and EGF domain. We analyzed the structure-function relationships of Vn by assaying deletion mutants. The results show that each conserved domain influences Vn activity. A PEST deletion increases Vn potency and genetic evidence suggests that Vn is regulated by proteasomal degradation. The Ig deletion causes toxic effects not seen following expression of native Vn, but the Ig domain is not required for Vn localization or for the activation of Egfr signaling in wing vein patterning. Remarkably, when the EGF domain is deleted, Vn functions as a dominant negative ligand, implying that Vn normally physically interacts with another factor to promote its activity. We identified additional highly conserved sequences and found several regions that affect Vn potency and one that may mediate the effect of dominant negative Vn molecules. Together the results show that the activity of Vn is controlled both positively and negatively, demonstrating the existence of additional levels at which Egfr signaling can be regulated.